Green Synthesis Of Silver Nanoparticles Using Ketapang Leaf Extract (Terminalia Catappa L.) Assisted By Ultrasound - Syaima, Husna; Hindryawati, Noor; Hiyahara, Irfan Ashari; Wirawan, Teguh; Arief, M. Syaiful; Widodo, Nanang Tri; Ahmad, Atika Aulia; Maniam, Gaanty Pragas (Universitas Negeri Semarang, 2023)
Green synthesis of silver nanoparticles using plants has been interesting in recent years. In the present study, the silver nanoparticles were synthesized using a bioreductor from ketapang leaf extract (Terminalia catappa L.) assisted by sonochemical methods. This green synthesis provides an economic, eco-friendly, and clean synthesis route for silver nanoparticles. Different concentrations of AgNO3 precursors (0.5; 1.0 and 1.5 mM) were initially reacted with ketapang leaf extract with PVA 1% solution as stabilizers that were sonicated for 30 minutes. Silver nanoparticle colloidal solutions were characterized using UV-Vis spectrophotometers, Particle Size Analyzers (PSA), and Transmission Electron Microscopes (TEM). Maximum absorption of silver nanoparticles was obtained at wavelength 420-450 nm. Based on UV data, the silver nanoparticles showed stability for up to 3 weeks. The XRD peaks indicated that the (111) crystallographic plane was more predominant than other planes. The average size of the silver nanoparticles was 79.7 nm from the PSA result. TEM imaging depicted that the nanoparticles were spherical. Finally, the result proved that the silver nanoparticles effectively removed the methylene blue up to 76.43% within optimum conditions (3 ppm of methylene blue, 15 minutes contact time, and 8% nanoparticle concentration).